Impact of repeat computerized tomography replans in the radiation therapy of head and neck cancers - Bhandari, Virendra (Medknow Publications & Media Pvt Ltd, 2014)
Anatomical changes can occur during course of head-and-neck (H and N) radiotherapy like tumor shrinkage, decreased edema and/or weight loss. This can lead to discrepancies in planned and delivered dose increasing the dose to organs at risk. A study was conducted to determine the volumetric and dosimetric changes with the help of repeat computed tomography (CT) and replanning for selected H and N cancer patients treated with IMRT plans to see for these effects. In 15 patients with primary H and N cancer, a repeat CT scan after 3(rd) week of radiotherapy was done when it was clinically indicated and then two plans were generated on repeat CT scan, actual plan (AP) planned on repeat CT scan, and hybrid plan (HP), which was generated by applying the first intensity-modulated radiation therapy (IMRT) plan (including monitoring units) to the images of second CT scan. Both plans (AP and HP) on repeat CT scan were compared for volumetric and dosimetric parameter. The mean variation in volumes between CT and repeat CT were 44.32 cc, 82.2 cc, and 149.83 cc for gross tumor volume (GTV), clinical target volumes (CTV), and planning target volume (PTV), respectively. Mean conformity index and homogeneity index was 0.68 and 1.07, respectively for AP and 0.5 and 1.16, respectively for HP. Mean D(95) and D(99) of PTV was 97.92% (standard deviation, SD 2.32) and 93.4% (SD 3.75), respectively for AP and 92.8% (SD 3.83) and 82.8% (SD 8.0), respectively for HP. Increase in mean doses to right parotid, left parotid, spine, and brainstem were 5.56 Gy (D(mean)), 3.28 Gy (D(mean)), 1.25 Gy (D(max)), and 3.88 Gy (D(max)), respectively in HP compared to AP. Repeat CT and replanning reduces the chance of discrepancies in delivered dose due to volume changes and also improves coverage to target volume and further reduces dose to organ at risk.